Treatment of Anorexia Nervosa in an Ultra-Orthodox Adolescent Male - Golan, Moria; Tepper, Sigal (Archives of Clinical and Medical Case Reports, 2019)
Objective: This unique case presents an opportunity to deepen the understanding of the etiology of anorexia nervosa in an ultraorthodox 14-year-old boy. The boy arrived at our countryside clinic after a 1.5-year history of severe self-imposed diet restrictions to control his weight and appearance, and a year of partial and full hospitalizations in psychiatric wards. The main objectives of the intervention were to achieve nutritional rehabilitation, normal eating habits and self-care, eliminate bed- wetting, and challenge developmental issues as well as cultural discourses. Method: 12-months of comprehensive intervention, which included a weekly dietetic session and parental guidance or family therapy, interpersonal and narrative psychotherapy twice a week, and a clinical mentorship (two days per week). His process was assessed via interview, using EDEQ-17 for the assessment of eating disorders, Das-21 for the assessment of self-regulation, Rosenberg scale for the assessment of self-esteem. Results: After a year in our outpatient clinic, he regained normal eating habits and weight status. His EDEQ global score was reduced from 4.1 to 0.9. His global DAS 21 score decreased from 38 (sever) to 7 (normal) indicating improvements in self-regulation and impulsiveness. Self-care & self-esteem were also significantly improved. The bed-wetting disappeared. He is currently fully functional in his community and attends a school that better accommodates him. The co-morbidity of eating disorders, obsessive-compulsive symptoms, impulsiveness and anxieties as well as bed-wetting demanded an intene and long-lasting intervention. Discussion: The described case demonstrates the dynamic of being "unfit” for ideal functioning in the ultraorthodox community as a precursor for anorexia nervosa with compulsive features. The co-morbidity of